Convenient Synthesis of Ethyl 5-Oxohomoadamantane-4-carboxylate: A Useful Precursor of Polyfunctional Homoadamantanes - Tkachenko, Ilya M.; Rybakov, Victor B.; Klimochkin, Yuri N. (Synthesis, 2019)
A facile and convenient synthesis of ethyl 5-oxohomoadamantane-4-carboxylate is reported, and its chemical properties as a cage analogue of acetoacetic ester are investigated. Various derivatives of homoadamantane were synthesized through the reaction of 5-oxohomoadamantane-4-carboxylate with electrophilic agents, binucleophiles, and hydrazoic acid. Some new unusual products were obtained by the reaction of that β-keto ester with nitric acid and nitrosyl chloride. Cage compounds synthesized could be used as precursors for the diverse condensed heterocyclic compounds with potential viral ion channel abrogating activity that possess conformationally rigid lipophilic moieties.
Keywords: cage compounds; homoadamantane; β-keto ester; homologation; tetrazole